Avaliação dos impactos da urbanização sobre as comunidades de macroalgas bentônicas no litoral do Espírito Santo, Brasil - CARVALHO, Vanessa Freire de (2013)
The impacts caused by the urbanization have led to the decline of macroalgal biodiversity worldwide. This work aimed to study the impacts of urbanization on macroalgal communities on the coast of Espírito Santo. Nine areas were chosen for the surveys, four in urban centers and five distant from urban centers. The sampling procedures were made in consolidated substrates, on the intertidal zone during low tides. Photoquadrats were used for sampling. In each area three transects were positioned parallel to the coast and 30 quadrats were plotted to determine macroalgal percent cover. In each area macroalgae samples were collected for identification. The ecological indices: Shannon-Wiener, Margalef and Pielou evenness, were calculated and this data was used to perform the analysis of similarity (ANOSIM) and analysis of variance (ANOVA). 125 species were identified, of which 75 were Rhodophyta, 30 Chlorophyta and 20 Heterokontophyta (Phaeophyceae). Species of the genus Ulva, Colpomenia sinuosa and Arthrocardia variabilis were the dominant species in urban beaches, while Palisada perforata, Amphyroa anastomosans and Codium intertextum dominated in reference areas. Both the analysis of qualitative as quantitative similarity showed significant differences between the areas. The ANOVAS showed that Ilha do Frade have the lowest species richness. Ilha do Frade and Ilha do Boi, located in Vitória city, the state capital, showed the lowest diversity. The results show differences in the composition of macroalgal communities between urban and reference beaches of the coast of Espírito Santo.